Dexamethasone inhibits inflammation and cartilage damage in a new model of post‐traumatic osteoarthritis. Issue 4 (30th December 2013) - Huebner, Kyla D.; Shrive, Nigel G.; Frank, Cyril B.
ABSTRACT Corticosteroids are used in musculoskeletal diseases, and offer patient relief. Injections of corticosteroids are recommended for management of osteoarthritis (OA). Current data have shown the role of corticosteroids in ameliorating pain. We hypothesized that repeated intra‐articular injections of high dose dexamethasone would protect the cartilage from damage in a post‐traumatic model of OA. Eighteen female New Zealand White rabbits were used. Twelve underwent surgery to induce OA; six of them received intra‐articular injections of dexamethasone every 3 days for 3 weeks. The other six rabbits served as operated controls. Six additional rabbits served as non‐operated controls. All animals were euthanized 3 weeks post‐surgery. Knees were assessed grossly. Cartilage, synovium, and fat pad were assessed histologically. Synovium and fat pad were analyzed with qPCR and Western blots. Surgical controls had cartilage damage which was supressed with dexamethasone. Dexamethasone significantly decreased synovial expression of interleukin‐1β and collagen I, and a trend to decrease synovial matrix metalloproteinase3 expression. There were also significantly lower levels of interleukin‐1β protein with dexamethasone treatment. Dexamethasone significantly decreased fat pad expression of matrix metalloproteinase13, basic fibroblast growth factor, and interleukin8, and a trend to decrease matrix metalloproteinase3 and transforming growth factorβ expression. Dexamethasone decreased joint inflammation and joint tissue degradation and was chondroprotective in this unique model of PTOA. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:566–572, 2014.